2019
DOI: 10.54530/jcmc.17
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Job Satisfaction Among Nurses Working in Teaching Hospital, Chitwan, Nepal

Abstract: Background: Job satisfaction is a major factor in nurse retention and the delivery of high quality care. Hence, aim of this study was to find out the factors affecting job satisfaction among nurses working in the teaching hospital, Chitwan. Methods: A descriptive, cross-sectional research design was used and a total 135 nurses who were working for at least 3 months in the Chitwan Medical Teaching Hospital were taken as study sample. Simple random sampling technique was used to select the desired sample. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 2 publications
(4 reference statements)
1
2
0
Order By: Relevance
“…10 Similar findings were reported in study by Poudel that revealed nurses were dissatisfied with their salary and benefits. 22 Similar findings were reported in study by Shah that revealed nurses were dissatisfied with their salary and employment benefits. 23 The finding of study revealed that more than half of the respondents (54%) had total stress score more than mean of total stress score i.e.…”
Section: Discussionsupporting
confidence: 82%
“…10 Similar findings were reported in study by Poudel that revealed nurses were dissatisfied with their salary and benefits. 22 Similar findings were reported in study by Shah that revealed nurses were dissatisfied with their salary and employment benefits. 23 The finding of study revealed that more than half of the respondents (54%) had total stress score more than mean of total stress score i.e.…”
Section: Discussionsupporting
confidence: 82%
“…For example, a research conducted by Shrestha et al [21], showed that individuals who viewed themselves as significant assets to the healthcare system reported greater levels of work satisfaction. In a similar vein, another study discovered that organizational and administrative policies have a significant role in forecasting levels of work satisfaction [22]. Similarly, a prior study, showed that nurses job satisfaction was influenced by several factors, including interpersonal connections, physical infrastructure, working environment, financial and non- [23].…”
Section: Introductionmentioning
confidence: 81%
“…Previous research has dedicated significant attention to the examination of work-family conflict [17][18][19] and the role of social support [20]. A substantial body of nursing literature in Nepal has conducted comprehensive investigations on the topic of work satisfaction [21][22][23][24][25][26][27]. For example, a research conducted by Shrestha et al [21], showed that individuals who viewed themselves as significant assets to the healthcare system reported greater levels of work satisfaction.…”
Section: Introductionmentioning
confidence: 99%